Challenges and Opportunities Implementing an ePortfolio Approach to Interprofessional Health Education in Australia - Bathgate, Katherine; Harris, Courtenay; Comfort, Jude; Oliver, Beverley (University of Arizona, 2011)
Background/Rationale: The assurance of learning of key capabilities and competencies by university graduates is a world-wide movement: measures such as the Collegiate Learning Assessment (Hardison & Vilamovska, 2009) attempt to report quantitative measures. In recent years there has been growing interest in capturing broader and, in the United States, essential learning outcomes (Association of American Colleges and Universities, 2004) and learning over time through ePortfolios (Rhodes, 2011). In Australia, universities have implemented graduate attributes (Coates, 2010). Curtin University has a whole of curriculum approach to mapping and evaluating achievement, and focal to this is its newly implemented iPortfolio (Oliver, 2009). Methods/Methodology: The Health Sciences faculty has recently implemented an interprofessional capability framework, and an interprofessional first year curriculum. Curtin University’s iPortfolio is an online space for students and staff to create, share and publish evidence of their learning achievements and professional development. It provides social networking features that encourage students to seek feedback from on their work and achievement of learning outcomes. iPortfolio has been utilised in one of the large (1800 student) first semester units Foundations for Professional Health Practice 100 as a tool for evaluating student development of key professional skills and as a means of giving and receiving feedback from an interprofessional peer learning group.Results: Early anecdotal evidence suggests that despite the challenges of introducing new technology to a large cohort, students engaged with the technology and are using it effectively to reflect on their learning. There were several challenges introducing iPortfolio which were faced by staff and students however through communication and responsiveness of information technology staff these were overcome. Conclusion: Introducing new iPortfolio technology into a new large interprofessional unit brings challenges which when overcome lead to unique and exciting opportunities for collaboration and learning in interprofessional peer learning groups in health.